A Preliminary Study of Proteomic Analysis on Caseins and Whey Proteins in Donkey Milk from Xinjiang and Shandong of China. Issue 1 (2nd March 2021) - Luoyizha, Wahafu; Zeng, Bo; Li, Hui; Liao, Xiaojun
Abstract : The proteomics of donkey milk from China's major producing areas have not been well documented. To explore the protein profiles of donkey milk from China, this study preliminarily investigated caseins and whey proteins in products from two major producing areas using quantitative proteomics approach. Total 15 caseins genetic variants and 620 whey proteins were identified and relatively quantified. Functional categorization of whey proteins was clustered into 46 terms based on Gene ontology (GO) and 42 Brite B classes based on Kyoto Encyclopedia of Genes and Genomes (KEGG). Six of the seven identified isoforms of caseins were firstly observed in donkey milk. Whey proteins including α ‐lactalbumin, β ‐lactoglobulins and lysozyme were identified, but no immunoglobulins or lactoferrin was determined. An unprecedented low ratio of casein/whey indicated that the products were very good sources with high biological value. This study enhanced knowledge of protein composition and established proteins profiles of differentially expressed proteins in the selected products of donkey milk from China. GRAPHICAL ABSTRACT: